Teachers’ Religious Commitment and Work Performance in Public Schools - D. Maculada, Romel; S. Guanzon, Renith (Polaris Global Journal of Scholarly Research and Trends, 2024)
A systematic examination of the relationship between teachers’ religious commitment and work performance in public schools offers valuable insights to the fields of education, psychology, and sociology, while also informing efforts to support the professional development and well-being of educators. In this context, this study aimed to determine the level of teachers’ religious commitment and work performance in all public elementary and secondary schools in a District in a second-class Municipality in Southern Negros Occidental during the School Year 2022-23. Data for this descriptive study was collected from 125 respondents using a self-made survey questionnaire that has passed the rigorist tests of validity and reliability. The ensuing analysis showed a high level of teachers’ religious commitment and a very satisfactory level of teachers’ work performance during the School Year 2022-2023. Further analysis showed a significant relationship between teachers’ religious commitment and work performance. The findings of this study call for immediate attention to the need to strengthen the religious aspects of teachers regardless of their religious affiliation.